Hydrologic and water quality performance of a subsurface gravel wetland treating stormwater runoff. (15th November 2022) - Sullivan, Catherine; McDonald, Walter
Abstract: Subsurface gravel wetlands are an emerging type of green infrastructure that can be used to manage stormwater through the capture and slow release of runoff. They are unique to other types of green infrastructure in that they have a distinct fully saturated gravel layer below an occasionally saturated soil layer that influences pollutant removal processes. While they have been widely applied to treat wastewater, our understanding of their efficiency in treating stormwater with variable pollutant inputs is limited. To fill this gap, this study monitored the flow and water quality (total suspended solids, total nitrogen, total phosphorus, and chloride) in a subsurface gravel wetland in Oshkosh, Wisconsin at the influent, effluent, and in an observation well. Results from nine storm events indicated that the wetland had a median volume reduction of 74% and a median peak flow reduction of 89%. The reduction in pollutant concentrations where highly dependent upon the influent concentration. Average reductions of total suspended solids, total nitrogen, and total phosphorus were 49%, −21% and −0.2%, respectively, indicating an increase in nutrients; however, where influent concentrations were above irreducible levels, total phosphorus was reduced by 45% (influent ≥0.25 mg/L) and total nitrogen was reduced by 38% (influent ≥2.5 mg/L). Overall, this study shows that the subsurface gravel wetland performed similar to other types of green infrastructure and could be a good management practice to mitigate the harmful effects of stormwater runoff. Graphical abstract: Image 1 Highlights: Monitoring data of a subsurface gravel wetland that treats stormwater is presented. Volume of runoff and peak flows were reduced by 74% and 89% on average. Reductions in nutrient concentrations were dependent upon influent concentrations. Total phosphorus concentrations are reduced at influent ≥0.25 mg/L. Total nitrogen concentrations are reduced at influent ≥2.5 mg/L.